Impact of social media advertisement on brand loyalty With reference to soft drink marketing situations in Chitwan district (Nepalese Journal of Management Research, 2021)
Social media advertisement has great impact on the consumers loyalty. Factors affecting brand loyalty are quality of product as well as effective and entertaining social media advertisement. In the views of consumers best social media is Face Book rather than Instagram and Messengers most liked advertisement is Coke due to it entertaining advertisement in social media.